Throwing in the towel: What happens when analysts' recommendations go wrong? - Lee, Kenneth; Aleksanyan, Mark; Harris, Elaine; Manochin, Melina (Contemporary Accounting Research, 2023)
Abstract Every analyst will experience stock recommendation failures during their career. Unlike many other professions, these pivotal moments occur in the full glare of clients, colleagues, equity‐sales teams, and the media. This research explores the practices of analysts up to and beyond the point where, faced with a failing recommendation, they contemplate “throwing in the towel” on their recommendation. Based on empirical evidence gathered from interviews with sell‐side analysts and their key interlocutors—equity‐sales specialists, investors, and investor relations officers—this paper uncovers several new empirical insights into the recommendation practices of analysts. The main argument made in the paper is that capitulation practices emerge from the specific contextual framework of individual recommendations and the analyst's conduct as a knowledgeable, emotional human agent. We identify several contextual contingencies of stock recommendations that underpin how a capitulation episode unfolds, including the temporal proximity of the capitulation to the original recommendation; the importance and profile of the stock to the analyst's reputation (“franchise intensity”); the level of interest/reaction from clients, equity‐sales teams and corporates; the nature/cause of recommendation failure; and recommendation boldness. Our study provides evidence that what an analyst does when faced with a failing recommendation cannot be reduced to a predictable, rational process and informs our understanding of observed practices such as the reluctance of analysts to capitulate and why “recommendation paralysis” often follows a recommendation capitulation.